PENGARUH KUALITAS ANGGARAN DAN PENGENDALIAN ANGGARAN TERHADAP EFEKTIVITAS ORGANISASI DI LINGKUNGAN PEMERINTAHAN KOTA JAMBI - Sugiharto Sugiharto (Universitas Batanghari Jambi, 2014)
The purpose of this study is to analyze and demonstrate empirically on Effect of Budget and Budgetary Control Quality Organizational Effectiveness Against Government within the City of Edinburgh both partial as well . Techniques or methods used in collecting the data in the study with the technique or method of purposive random sampling ( purposive sampling / Judgement ) conducted by survey method by distributing research instruments / questionnaires to respondents from 39 on education in the workplace Jambi City Government 195 total questionnaires respondents . Distribution of 195 questionnaires , 163 were returned , which can not be processed 32 , and the data that can be processed is 158 questionnaire . Based on the analysis of the data obtained in the description of the results is that the partial hypothesis testing ( t-test ) showed that the partial hypothesis 1.1 which states that the quality of the budget significantly affect the effectiveness of government organizations and the provincial city hypothesis stating 1.2 budgetary control to significantly affect the effectiveness of government organizations Jambi city is evidenced by the t-test value at α 0.05 is above 1,725 t count on the quality of the budget and budget control 6.195 6.670 . Simultaneous testing ( Test - F ) , i hypothesis 2 which states that the quality of budget and budgetary control to significantly affect the effectiveness of government organizations Jambi city was evident with the calculated value of F - test results on the α - F 3.14 0.05 above that 163.627 . The role of the quality of budget and budgetary control that influence organizational effectiveness in the provincial city administration has been shown by the evidence that the factors contained in the variable quality of budget and budgetary control is able to significantly positively encourage the creation of organizational effectiveness .Keyword : Quality Budget, Budgetary Control and Organizational Effectiveness.